Upaya Peningkatan Kinerja Guru Dalam Menyusun Perangkat Administrasi Melalui Workshop Guru Di SMPN 29 - Lily Handasah (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2022)
This research is to examine efforts to increase the capacity of teachers at SMP Negeri 29 South Jakarta in the implementation of Management Standards, and must focus more on improving the quality of human resources, especially increasing the ability of teachers at SMP Negeri 29 South Jakarta in implementing Management Standards. School Action Research (PTS) was designed in two cycles, from the stages of planning, implementing, observing, and reflecting. The subjects of this study were 28 teachers at SMP Negeri 29 South Jakarta. Methods of data collection through observation sheets and documentation. The results of the research implementation show that the assessment of the Accreditation Administration Tool in the initial conditions average value of 60.00 and is included in the Enough category, in the first cycle the average value of acquisition is 69.33 and is still in the Enough category, while in the second cycle both acquisitions have an average acquisition value of 85.00 and are still in the Good category. There is an increase of 15.07 points, from cycle I to cycle II. Assessment of the implementation of Management Standards in the initial conditions the average value was 58.57 and included in the Enough category, in the first cycle the average acquisition value was 69.52 and still included in the Enough category, while in the second cycle the average value was the acquisition was 87.50 and still included in the Very Good category, there was an increase from cycle I to cycle II, which was 17.98 points.